Christianizing the Social Order: T.B. Kilpatrick's Theological Vision of the United Church of Canada - Fraser, Brian John (Toronto journal of theology, 1996)
While serving as a chaplain during World War I, George G.D. Kilpatrick wrote to his father that he found the men in the Canadian forces "reaching and groping for a coherent interpretation of inner experience." The elder Kilpatrick must have felt considerable disappointment in his son's assessment of the faith of Canadians at the front, for Thomas Buchanan Kilpatrick had spent a lifetime attempting to provide just such an interpretation of the meaning of humanity's experience of God, sin and redemption. Kilpatrick was one of Canada's most prominent Presbyterian theologians and an ardent supporter of church union. His understanding of the theological foundations of the United Church of Canada was widely shared by the leadership of the movement and represents one of the central paradigms within which the new church understood its mission of Christianizing the social order. This essay examines the nature of Kilpatrick's theological vision, focusing on his exposition of the doctrinal section of the Basis of Union of the United Church of Canada in the context of his interpretation of World War I.